2022
DOI: 10.1002/hpja.647
|View full text |Cite
|
Sign up to set email alerts
|

Patient requests for radiological services: An Australian study of patient agency and the impact of online health information

Abstract: Issue Addressed The Internet has been instrumental in patients' knowledge about health and medicine through increasing consultation of online sources that advocate self‐management. For example, those patients who request referrals from their doctors for tests and procedures in radiology. Such patient‐initiated referral requests can devolutionise the traditional model of health care. This study aimed to understand individuals who sought online health information (OHI) and whether requests for radiological refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…But some participants understood the doctors' gatekeeping role and tried to remain 'a patient' (Kravitz et al 2003). However, overall, seeing a doctor seems to have become a formality to secure a referral letter, rather than relying on the doctors' knowledge and guidance (De Silva et al 2023). This study, albeit small, found that doctors, in competing for patient satisfaction, maintaining relationships and keeping pace with clinical productivity, tend to adopt a default approach of agreeing to patient requests (Sabbatini et al 2014;Carey et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…But some participants understood the doctors' gatekeeping role and tried to remain 'a patient' (Kravitz et al 2003). However, overall, seeing a doctor seems to have become a formality to secure a referral letter, rather than relying on the doctors' knowledge and guidance (De Silva et al 2023). This study, albeit small, found that doctors, in competing for patient satisfaction, maintaining relationships and keeping pace with clinical productivity, tend to adopt a default approach of agreeing to patient requests (Sabbatini et al 2014;Carey et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to find, evaluate, and use online health information may be affected by an individual’s electronic health literacy (eHealth literacy) level ( 2 ) , which ensures the effective use of health information. eHealth literacy is defined as “the ability to seek, discover, understand, and evaluate health information from electronic sources, and apply the acquired knowledge to solving or solving health problems.” ( 3 ) Studies showed that people with high eHealth literacy were more likely to seek health information and health knowledge ( 4 ) , participate in health behaviors and screening practices ( 5 ) , and had better self-management skills and interactions with doctors ( 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…eHealth literacy is defined as "the ability to seek, discover, understand, and evaluate health information from electronic sources, and apply the acquired knowledge to solving or solving health problems." (3) Studies showed that people with high eHealth literacy were more likely to seek health information and health knowledge (4) , participate in health behaviors and screening practices (5) , and had better self-management skills and interactions with doctors (6) .…”
Section: Introductionmentioning
confidence: 99%